MENERAPKAN ETIKA NILAI MAX SCHELER DALAM PERKULIAHAN PENDIDIKAN PANCASILA UNTUK MEMBANGUN KESADARAN MORAL MAHASISWA - Wahana, Paulus (Jurnal Filsafat "WISDOM", 2016)
The universities, not only can develop the academic skill, also give lectures that are able to build the students' characters in complete. Pancasila Education, one of the subjects of character building, is hoped to be able to build the students' moral consciousness to create a high qualified life that is in accordance with Pancasila. Max Scheler is a moral philosopher who offers the material valueethic; offers the values as the basis thought for human action. According to Max Scheler's thought, the basic moral action of human beings hopefully does not stop at the consciousness to seek personal enjoyment (hedonist), and at the consciousness to obey the rules and do the obligations (deontologist), but do moral action based on their consciousness to create positive, high and objective values in human life. This piece of writing is aimed to explain the application of the Max Scheler's value-ethic as a base for Pancasila Education lecture to build students' moral consciousness. The students' moral consciousness is not only based on the moral consciousness to seek personal enjoyment and the obedience to regulations or institutions, but also the consciousness of the existence of a moral obligation to create positive, high and objective values in human life i.e. the high values of Pancasila.